Campaigning to win (Consultants Bureau, Instructech, 1992)
"Campaigning to win is a political handbook for political campaigners. Chapter I describes the legal context of elections as well as the different aspects of a political campaign. Chapter 2 shows how a political machinery may be organized and mobilized. The various ways of testing the political climate for one's candidacy are explained in Chapter 3. In Chapter 4, the different parts of a campaign plan are taken up while Chapter 5 gives tips on how to implement a widely tested campaign strategy."